2003
DOI: 10.1191/0143624403bt073oa
|View full text |Cite
|
Sign up to set email alerts
|

Improved methods for evaluating base temperature for use in building energy performance lines

Abstract: The use of degree-days in building energy monitoring and targeting has often given rise to misinterpretation of results, which has in turn undermined condence in such techniques. Anecdotal reporting has, by turns, suggested the use of degree-days either works very well, or does not work at all. This ambiguous position is not helpful to energy managers who need robust tools and clear guidance on their use. This paper presents evidence to show how energy/degree-day correlations i.e., building performance lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…The internal air temperature, (ºC), of a typical unheated English house is, on average, approximately 3ºC higher than ; the difference is attributable to solar and casual heat gains and fabric properties that affect heat transfer and thermal inertia. Therefore, the heating system is assumed to function only when is at least 3ºC below [29][30][31]. Equation (3) is integrated over the entire heating season to estimate the total heat loss, (kWh) via exfiltration.…”
Section: Modelling Infiltration and Exfiltration Heat Lossmentioning
confidence: 99%
“…The internal air temperature, (ºC), of a typical unheated English house is, on average, approximately 3ºC higher than ; the difference is attributable to solar and casual heat gains and fabric properties that affect heat transfer and thermal inertia. Therefore, the heating system is assumed to function only when is at least 3ºC below [29][30][31]. Equation (3) is integrated over the entire heating season to estimate the total heat loss, (kWh) via exfiltration.…”
Section: Modelling Infiltration and Exfiltration Heat Lossmentioning
confidence: 99%
“…for the particular region [17]. The use of building specific base temperature is, therefore, important for correct energy/degree-days correlations and should take into account the correct (and practical) energy balance of the building [27]. For this reason degree-days are calculated in this research at variable base temperatures ranging from 10°C to 20°C for heating and 10°C to 28°C for cooling degree-days at an interval of 0.5°C.…”
Section: Determining the Base Temperaturementioning
confidence: 99%
“…For this reason degree-days are calculated in this research at variable base temperatures ranging from 10°C to 20°C for heating and 10°C to 28°C for cooling degree-days at an interval of 0.5°C. The determination of building specific base temperature is out of scope of this paper; however, discussions on methods such as the use of building performance lines can be found in [16,27].…”
Section: Determining the Base Temperaturementioning
confidence: 99%
“…It is found that this variance is not always strictly random: it is likely to be caused by many other unmeasured disturbances or, for degree-days, a poor choice of base temperature [4]. Improved methods of modelling this consumption variance will be illustrated, with the purpose of improving Nomenclature B…”
Section: Introductionmentioning
confidence: 99%